Post-surgery Rehabilitative Intervention Based on Imitation Therapy and Mouth-Hand Motor Synergies Provides Better Outcomes in Smile Production in Children and Adults With Long Term Facial Paralysis - De Stefani, Elisa; Barbot, Anna; Zannoni, Cecilia; Belluardo, Mauro; Bertolini, Chiara; Cosoli, Rita; Bianchi, Bernardo; Ferri, Andrea; Zito, Francesca; Bergonzani, Michela; Schiano Lomoriello, Arianna; Sessa, Paola; et al. (Frontiers in Neurology, 2022)
Rehabilitation after free gracilis muscle transfer (smile surgery, SS) is crucial for a functional recovery of the smiling skill, mitigating social and psychological problems resulting from facial paralysis. We compared two post-SS rehabilitation treatments: the traditional based on teeth clenching exercises and the FIT-SAT (facial imitation and synergistic activity treatment). FIT-SAT, based on observation/imitation therapy and on hand-mouth motor synergies would facilitate neuronal activity in the facial motor cortex avoiding unwanted contractions of the jaw, implementing muscle control. We measured the smile symmetry on 30 patients, half of whom after SS underwent traditional treatment (control group, CG meanage = 20 ± 9) while the other half FIT-SAT (experimental group, EG meanage= 21 ± 14). We compared pictures of participants while holding two postures: maximum and gentle smile. The former corresponds to the maximal muscle contraction, whereas the latter is strongly linked to the control of muscle strength during voluntary movements. No differences were observed between the two groups in the maximum smile, whereas in the gentle smile the EG obtained a better symmetry than the CG. These results support the efficacy of FIT-SAT in modulating the smile allowing patients to adapt their smile to the various social contexts, aspect which is crucial during reciprocal interactions.